ANDROID-BASED MOBILE APPLICATION DEVELOPMENT EXPENSIFY: PERSONAL EXPENSE MANAGER - Rizki Fajar Maulian; Ronny Juwono (President University, 2022)
Personal financial management is no lessimportant to achieve personal prosperity. By planning,managing, and controlling their finances wisely andcarefully, each individual can consider their currentfinancial needs and conditions, to determine futurefinancial goals. By having financial planning, eachindividual can manage their financial resourcesoptimally to achieve the desired financial goals.However, there are still many individuals who are stillnot able to manage their finances properly. In additionto a lack of knowledge in managing personal finances,consumptive behaviour is also a contributing factor.One effort that can be done to overcome this is bymaking financial records, by recording daily expensesand income, individuals can more easily control andmanage their finances. This study aims to develop anAndroid-based personal expense managementapplication using the Kotlin programming language.This application has features that can assist users inmanaging their finances that can be used anywhereand anytime.